Comunidade ética: reconhecimento, consenso e sociedade em Henrique Cláudio de Lima Vaz - Sousa, Maria Celeste de (2009)
The thesis titled Ethic Community (Recognizability, Consensus, Society) in Henrique Claudio de Lima Vaz aims to present the Vazian reflection on intersubjective relation according to its ontological, reflexive and ethic expression. It is an interpretation of the intersubjectivity category considering its social, political, democratic and ethic developments. The main philosophical issue is: How should we shape our lives? Lima Vaz revisits now this classical question because he is aware of the pervasive revolution that is reshaping human societies in the last two centuries. Lima Vaz reflects mainly on the phenomena of solipsism and ethical nihilism that is spreading vertiginously to all fields of ideas and values found in the occidental tradition within a society that has become predominantly dominated by science and technology. He assess this reality according to the Hegelian model in order to surpass the finite circle where reason in its modern fashion is found, and recapture the analogical conception of being from the philosophical tradition. In his two books, Philosophical Anthropology and A Philosophical Introduction to Ethics he updates the logic-ontological features of human nature according to its constituting sociability, focusing on the idea of Community and developing it according to the law of dialectical circularity in order to demonstrate human relational experience as a whole within the three logical circles of knowledge (being), consensus (essence) and society (existence) in a manner that emulates Hegel s Philosophy of the Objective Spirit. The thesis expounds systematically the logical determinations of the relational experience which in Lima Vaz s interpretation, man considers himself as an essentially communal being